Pemanfaatan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) sebagai Sumber Antioksidan Alami dalam Formulasi Kefir Susu Sapi - Yola Desnera Putri; Restiani Novitasari; Sohadi Warya; Adit Andriyannto (Nutrition Science and Health Research, 2026)
Kefir is a fermented beverage rich in probiotics with potential antioxidant activity capable of scavenging free radicals. In order to enhance its antioxidant activity, this study utilized red dragon fruit peel extract (Hylocereus polyrhizus), which is known to contain polyphenolic compounds as natural antioxidants. This study aimed to evaluate the effect of red dragon fruit peel extract fortification on the antioxidant activity and chemical characteristics of cow milk kefir. The research methods included extraction and phytochemical screening, preparation of kefir with different extract concentrations (0.002%, 0.1%, and 0.2%), antioxidant activity assessment using the DPPH method, and chemical analysis including pH, protein content, fat content, and lactic acid content, which were performed on the formulation with the highest antioxidant activity. All analyses were conducted in triplicate (n=3). The results showed that the red dragon fruit peel extract contained polyphenols, flavonoids, tannins, and quinones. The extract exhibited an IC₅₀ value of 19.96 μg/mL, while the unfortified kefir showed an IC₅₀ value of 93.96 μg/mL. Fortification of kefir with the extract increased antioxidant activity, as indicated by decreasing IC₅₀ values of 75.47 μg/mL (0.002%), 37.28 μg/mL (0.1%), and 29.61 μg/mL (0.2%). These findings indicate that increasing extract concentration enhances the antioxidant activity of kefir. Kefir fortified with 0.2% extract exhibited the following chemical characteristics: pH 4.51, protein content 3.84%, fat content 5.67%, and lactic acid content 1.24%, all ofwhich complied with the quality standards of kefir according to CODEX STAN 243-2003. In conclusion, fortification with red dragon fruit peel extract has the potential to enhance the antioxidant activity of cow milk kefir without compromising its chemical quality, suggesting its potential application as a functional food.